Mulher acometida pelo papilomavírus humano e repercussões na família - Joca, Mirella Teixeira (2007)
Human Papillomavirus (HPV) is one viral agent that causes infective disease, of transmission frequently sexual, known usually as acuminated conduloma, genital wart or cockscomb, it is the main agent that causes the cancer of the uterus colon as sure as can be with repercussion in the life of the infected individual and in the health of the family. The aims were to evaluate the structure, the development and the function of the family composed by attacked woman by Human Papillomavirus, based in the Calgary Model; to identify possible influences caused within structural family due to disease; to identify factors that the woman relates with the cause of the disease. The search was the descriptive type with qualitative boarding, having been realized one case study, at the home of the informer making use of the Calgary Model as one touched topic of family valuation. Datum collection was realized in January and February from 2007, through interview semi-structured with the couple, genogram and echomap from family. The family was composed of four members such as: the couple Josué and Rosa and their two children: Gabriel and Bela. By gynecological routine exam it was diagnosed in Rosa, one external wart and one small lesion in the scale-columnar junction of the uterus colon. All the members of the family maintain healthy relationship among them; there is a little bit of negativity in the entail between Rosa and Gabriel, due to charges with relation to studies. The couple didn’t keep away from their social net, due to undertaking with the virus. The housewife shared the case with her husband, accusing him, but lately she got acquired him of the importance from safe sexual habits. The couple got over comes the grasped critical phases, overlooking as better repercussion, the changing of their habits and bigger affection among the family. With regard to the theme HPV, it had seen that many people unknown still, staying to the load from professional spread the subject with more emphasis as among women well as men. As well as to promote the education within health, in order to the people reflect to respect of the great importance in utilizing the prophylactic.